2021
DOI: 10.1101/2021.06.22.21259346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can Auxiliary Indicators Improve COVID-19 Forecasting and Hotspot Prediction?

Abstract: Reliable, short-term forecasts of traditional public health reporting streams (such as cases, hospitalizations, and deaths) are a key ingredient in effective public health decision-making during a pandemic. Since April 2020, our research group has worked with data partners to collect, curate, and make publicly available numerous real-time COVID-19 indicators, providing multiple views of pandemic activity. This paper studies the utility of these indicators from a forecasting perspective. We focus on five indica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…An observational study could be conducted with forecasts collected by the Hub, but any such analysis would be confounded by other factors about how the model was built and validated. Other research in this area has shown small but measurable improvements in predictive accuracy by including other data streams available in real time ( 23 ). Continued research is needed to evaluate how behavioral, mobility, variant prevalence, or other data streams might enhance predictive modeling…”
Section: Discussionmentioning
confidence: 99%
“…An observational study could be conducted with forecasts collected by the Hub, but any such analysis would be confounded by other factors about how the model was built and validated. Other research in this area has shown small but measurable improvements in predictive accuracy by including other data streams available in real time ( 23 ). Continued research is needed to evaluate how behavioral, mobility, variant prevalence, or other data streams might enhance predictive modeling…”
Section: Discussionmentioning
confidence: 99%
“…The indicators enumerated in Section 2 have displayed impressive correlations to reported COVID-19 cases (Reinhart et al, 2021), and moreover, demonstrated an ability to improve the accuracy of case forecasting and hotspot prediction models (McDonald et al, 2021). In this section, we describe how to use each indicator to build a real-time sensor that estimates the latent infection rate, and how to fuse such estimates together into a single nowcast.…”
Section: Leveraging Auxiliary Signalsmentioning
confidence: 99%
“…For more information on CTIS in particular, we refer to Salomon et al (2021). For a study of how these and similar indicators can contribute to COVID-19 forecasting models, we refer to McDonald et al (2021).…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group of models uses geographic and aggregate mobility data and mechanistic transmission models such as SEIR to predict population incidence and hospitalization rates [17,18,19]. In terms of short-term predictions, two recent novel approaches include utilizing small area data together with empirical models to make short-term predictions [20] and using auxiliary indicators [21].…”
Section: Introductionmentioning
confidence: 99%